Altering the redox state of skeletal muscle by glutathione depletion increases the exercise‐activation of PGC‐1α. Issue 12 (23rd December 2014) - Strobel, Natalie A.; Matsumoto, Aya; Peake, Jonathan M.; Marsh, Susan A.; Peternelj, Tina‐Tinkara; Briskey, David; Fassett, Robert G.; Coombes, Jeff S.; Wadley, Glenn D.
Abstract We investigated the relationship between markers of mitochondrial biogenesis, cell signaling, and antioxidant enzymes by depleting skeletal muscle glutathione with diethyl maleate (DEM) which resulted in a demonstrable increase in oxidative stress during exercise. Animals were divided into six groups: (1) sedentary control rats; (2) sedentary rats + DEM; (3) exercise control rats euthanized immediately after exercise; (4) exercise rats + DEM; (5) exercise control rats euthanized 4 h after exercise; and (6) exercise rats + DEM euthanized 4 h after exercise. Exercising animals ran on the treadmill at a 10% gradient at 20 m/min for the first 30 min. The speed was then increased every 10 min by 1.6 m/min until exhaustion. There was a reduction in total glutathione in the skeletal muscle of DEM treated animals compared to the control animals (P < 0.05). Within the control group, total glutathione was higher in the sedentary group compared to after exercise (P < 0.05). DEM treatment also significantly increased oxidative stress, as measured by increased plasma F2–isoprostanes (P < 0.05). Exercising animals given DEM showed a significantly greater increase in peroxisome proliferator activated receptor γ coactivator‐1α (PGC–1α) mRNA compared to the control animals that were exercised (P < 0.05). This study provides novel evidence that by lowering the endogenous antioxidant glutathione in skeletal muscle and inducing oxidative stress through exercise, PGC‐1α gene expression was augmented. These findings further highlight the important role of exercise induced oxidative stress in the regulation of mitochondrial biogenesis.